Integrating sustainable construction materials to achieve green building - Kasassbeh, A.; Al Omari, Omar; Suboh, M. (2015)
Green buildings integrate building materials and methods that promote environmental quality, economic vitality and social benefits through the design, construction and operation of the built environment. This study demonstrates potential actions including material selection that can be implemented to achieve green building. Also, we discuss the importance and environmental impact of sustainable material, the selection criteria of these materials and the different types of sustainable materials in the buildings construction in Jordan.